Low-Carbohydrate Ketogenic Diet for Improvement of Glycemic Control: Mechanism of Action of Ketosis and Beneficial Effects - Sakr, Hussein F.; Sirasanagandla, Srinivasa R.; Das, Srijit; Bima, Abdulhadi I.; Elsamanoudy, Ayman Z. (Current Diabetes Reviews, 2023)
The incidence of metabolic syndrome and diabetes mellitus is increasing globally. A diet rich in carbohydrates increases the hyperglycemic state. While considering the lifestyle changes to combat life-threatening diseases, there is an effort to decrease the daily intake of carbohydrates. A low-carbohydrate diet also makes the body rely more on fat for energy, so there is less fat accumulation. A diet is considered to be low-carbohydrate ketogenic if the intake is ≤ 50 g per day. The ‘low -carbohydrate ketogenic diet’ (LCKD) produces ketosis. LCKD contains high-fat, moderateprotein, and low-carbohydrate components. The main objectives of the present review are to discuss insulin resistance in different viscera of the body, describe the role of adipokines in insulin resistance, understand the mechanism of ketogenesis, and determine the impact of LCKD in overcoming insulin resistance in the body. In the present review, we also highlight the beneficial effects of LCKD in metabolic, neurodegenerative, cardiovascular, and lipid disorders and discuss the effect on longevity and aging. LCKD may help in combating the morbidity and mortality arising from the above-mentioned diseases and also help in leading a better quality of life.
Keywords: ketosis